PERAN BIG DATA DAN AUDIT FORENSIK TERHADAP PENDETEKSIAN FRAUD - Suci Rosa Pratiwi; Firman Surya; Dedy Djefris (Journal of Applied Accounting And Business, 2023)
The large number of fraud cases that occur is still a concern for many parties, so there is a need for action that can detect fraud. One effort that can be made to detect fraud is by utilizing technology through the role of big data. Apart from that, the use of forensic audit science can also be applied in an effort to detect fraud. This research aims to analyze the role of big data in forensic auditing, and this research was also carried out to analyze the role of big data and forensic auditing in fraud detection. The research method used is a survey method with a quantitative approach. The population of this study are auditors who work in Public Accounting Firms (KAP) which researchers can reach in DKI Jakarta, Pekanbaru and Surabaya. The type of data used is primary data and the sampling technique uses the snowball sampling technique with the number of respondents obtained being 132 respondents. Data collection was carried out by distributing questionnaires via Google Form which were distributed to auditors who worked at KAP. The data analysis method uses Structural Equation Modeling (SEM) with Partial Least Squares (PLS) technique. Data processing uses SmartPLS 3.0 software. The results of this research show that big data has a positive effect on forensic audits, big data has a positive effect on fraud detection, and forensic audits have no effect on fraud detection.